Abnormal Regenerative Responses and Impaired Axonal Outgrowth after Nerve Crush in TDP-43 Transgenic Mouse Models of Amyotrophic Lateral Sclerosis - Swarup, Vivek; Audet, Jean-Nicolas; Phaneuf, Daniel; Kriz, Jasna; Julien, Jean-Pierre (The Journal of neuroscience, 2012)
Tar DNA binding protein 43 (TDP-43) mislocalization and aggregation is a hallmark of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar dementia. Moreover, TDP-43 mRNA was found to be upregulated by ∼2.5-fold in the spinal cord of sporadic ALS subjects. Here we have examined the effects of nerve injury in new transgenic mouse models overexpressing by approximately threefold wild-type or mutant (G348C) TDP-43 species. Four weeks after axonal crush of sciatic nerve, TDP-43 transgenic mice remained paralyzed at the injured limb unlike control mice, which had regained most of their normal mobility. In contrast to normal mice, TDP-43 transgenic mice exhibited sustained elevation of TDP-43 cytoplasmic levels in motor neurons after nerve crush, and the relocalization of TDP-43 to the nucleus was delayed by several weeks. After crush, peripherin and ubiquitin levels remained also significantly elevated in TDP-43 transgenic mice compared with control mice. Analysis of the sciatic nerve at 11 d after nerve crush showed that the number of regenerating axons in the distal portion of the lesion was considerably reduced in TDP-43 transgenic mice, especially in TDP-43 G348C mice, which exhibited a reduction of ∼40%. In addition, markers of neuroinflammation were detected at much higher levels in TDP-43 transgenic mice. These results suggest that a deregulation of TDP-43 expression in ALS is a phenomenon that can affect the regenerative responses to neuronal injury and regrowth potential of axons.